Karst phenomena in the Karajogh Mountain region (a study in applied geomorphology) - الشمزينى, يوسف صالح إسماعيل; رحمان, كاوه جبار (Sulaimani Journal for Humanities, 2019)
This research deals with a (karst phenomenon in mount Qara chuq area) which is located to the southwest of the city of Erbil, between latitude (350 :34:31 - 360 :01:58) in the north, and longitude (430 :24:44 – 430 :54:14) in the east. Mount Qara chuq is characterized by the existence of a large number of karst phenomena. The aim of this study is to offer a geographical assessment of the reality of the karst phenomenon and the distribution in the area. We will also prepare a statement of the impact of natural and human factors on the karst phenomenon and highlight the problems that are created with regard to this phenomenon which is suffering as a result of population activities in the study area. We will consider ways to manage this problem and attempt to develop appropriate solutions using modern techniques. This will be an important tool in this study. This study attempts to answer several questions and show the validity of the proposed hypotheses. This is done through a comprehensive field survey of the karst phenomena undertaken by the researcher in the study area. This involves quantitative and descriptive method approaches, drawing on his production analysis. For the purpose of achieving the goals of this research and investigation in term of the hypothesis put forward as part of this research, this thesis contained three chapters. The first chapter discusses the analysis of natural environmental factors controlling the functioning and development of the karst phenomenon. The second chapter is devoted to producing a number of geomorphological maps, showing the types of karst phenomena together with the geographical distribution in this area. The third chapter consists of two sections. The first one is to assess the problems and environmental hazards associated with the karst phenomena, and providing solutions and treatments for such problems, while the second part deals with the administration of the karst phenomena. This study has reached a set of conclusions, the most important of which are as follows: – The study revealed that the compositional factor and the geological stratigraphy are the most important aspects associated with creating the karst phenomena. –The majority of karst phenomena developed due to the effects of rain period especially during the Pleistocene period. –The study area suffers with a number of environment problems which were created by karst phenomena such as landslides, cracks and agricultural problems due to groundwater contamination. –There are a number of caves in this area that are suitable for use for the purposes of tourism and by the military. –There are many springs suitable for use for the purpose of medical tourism.